A micro motion sensing system for micromanipulation tasks - Tan, U Xuan (2013)
An optical-based motion sensing system has been developed for real-time sensing of instrument motion in micromanipulation. The main components of the system consist of a pair of position sensitive detectors (PSDs), lenses, an infrared (IR) diode that illuminates the workspace of the system, a non-reflective intraocular shaft, and a white reflective ball attached at the end of the shaft. The system calculates 3D displacement of the ball inside the workspace using the centroid position of the IR rays that are reflected from the ball and strike the PSDs. In order to eliminate inherent nonlinearity of the system, calibration using a feedforward neural network is proposed and presented. Handling of different ambient light and environment light conditions not to affect the system accuracy is described. Analyses of the whole optical system and effect of instrument orientation on the system accuracy are presented. Sensing resolution, dynamic accuracies at a few different frequencies, and static accuracies at a few different orientations of the instrument are reported. The system and the analyses are useful in assessing performance of hand-held microsurgical instruments and operator performance in micromanipulation tasks.